SEMIOTIC CHARACTERISTICS IN ANVAR OBIDJAN'S LYRICS (Scientific journal of the Fergana State University, 2023)
The article aims to reflect on the structural changes that occurred in Uzbek poetry in the last quarter of the 20th century through the analysis of the three poems of the talented poet Anvar Obidjon. The relevance of the problem is explained in the introduction. In particular, it is based on the need to express a deep meaning with few words, to study the illumination of great artistic and social ideas in a three-line poem. The theoretical foundations of semiotics and the scientific-theoretical literature on structural analysis are discussed, and the methodology of the article is clarified based on the sources. Based on structural analysis, the role of semiotic features in lyrics is revealed.  For this purpose, the main results from the analysis of scientific literature have been defined. It is emphasized that every sign, sound, and word in the small poem encourages the reader to think associatively and thus deepens the content layer of the three-line poem. In the analytical part, three poems are analyzed, and it is scientifically proven that the poet's artistic and social ideas, lyrical experiences are expressed with the help of specific details and artistic code. During the analysis, the author is based on the scientific-theoretical opinions of well-known scientists such as Atoullah Husayniy, Nicola Bualo, Yuriy Lotman, Meneghetti Antonio. In the conclusion, the general conclusions reached during the research are presented in a concise form. At the end of the article there is a list of used literature in alphabetical order.